Analysis of elementary school students mathematical problem-solving abilities based on the IDEAL model stages - Asep Ahyar; Yunus Abidin; Yeni Yuniarti; Ai Sutini; Burieva Kibrio Ergashevna (DWIJA CENDEKIA: Jurnal Riset Pedagogik, 2026)
The mathematical problem solving abilities of elementary school students still show variations in achievement at each stage of problem solving. This study aims to map the mathematical problem solving abilities of fourth-grade elementary school students based on the five stages of the IDEAL model (Identify, Define, Explore, Act, Look Back). The study used a quantitative descriptive approach with total sampling of 24 students. The instrument was a contextual problem solving test assessed using an analytical rubric on a scale of 0–4 at each stage. The scores were analyzed through average calculations and conversion of ability categories. The results showed that the Act (2.79) and Explore (2.54) stages were in the capable category, while the Identify (2.46) and Define (2.33) stages were in the sufficient category, and the Look Back (1.92) stage was the weakest aspect. Overall, most students were classified as capable, but weaknesses were still found in the stages of formulating information and verifying solutions. These findings emphasize the importance of strengthening reflective strategies in mathematics learning. This IDEAL stage-based competency mapping can serve as the basis for more systematic problem solving learning planning in elementary schools.